Odpowiedzi

2009-12-07T20:01:56+01:00
A/ 4x²=(5-2x)²
4x² = 25 - 20x + 4x²
20x = 25
x = 1¼

b/ (2x-2)²=4x(x-4)
4x² - 8x + 4 = 4x² - 16x
8 x = -4
x = -½

c/ x(4x-3)=(2x-3)²
4x² - 3x = 4x² - 12x + 9
9x = 9
x = 1

d/ x(0,04x-1,3)=(0,2x-1)²
0,04x² - 1,3x = 0,04x² - 0,4x + 1
-0,9x = 1
x = -1i1/9
  • Użytkownik Zadane
2009-12-07T20:02:59+01:00
A/ 4x²=(5-2x)²
4x²=25-20x+4x²
4x²+20x-4x²=25
20x=25/:20
x=25/20
x=5/4
x=1 i 1/4

b/ (2x-2)²=4x(x-4)
4x²-8x+4 = 4x²-16x
4x²-8x-4x²-16x = -4
24x = -4 / :24
x = -4/24
x=-1/6
2009-12-07T20:07:02+01:00
A) 4x²=(5-2x)²
4x²=25+4x²
4x²-4x²=25
0=25

b/ (2x-2)²=4x(x-4)
4x²+4=4x²-16x
4x²-4x²-16x=-4
-16x=-4/:(-16)
x=0,25

c/ x(4x-3)=(2x-3)²
4x²-3x=4x²+9
4x²-4x²-3x=9
-3x=9/:(-3)
x=-3

d/ x(0,004x-1,3)=(0,2x-1)²
0,004x²-1,3x=0,2x²+2
0,004x²-0,004x²-1,3x=2
-1,3x=2/:(-1,3)
x=1,53